Development and characterization of biodegradable biorenewable polymeric nanocomposites for food packaging applications - Fadl, Samar Mohamed Ahmed (AUC Knowledge Fountain, 2015)
During the last 10 decades, plastic products have dominated humans’ lives with various applications in different fields, and particularly in food packaging industry. The fact that plastics do have numerous desirable characteristics does not conceal their detrimental effect on the environment and on human health. In order to overcome these problematic issues and to contribute to sustainable development in the future, other alternatives represented in employing biorenewable biodegradable polymers are implemented for plastics production. Poly (lactic acid) (PLA) is one of the most common employed biopolymer owing to its interesting characteristics. However, PLA exhibits poor mechanical and barrier properties. Natural plasticizers and nano-reinforcement are incorporated into PLA matrix in order to overcome its brittle nature and to improve its barrier properties, particularly for the purpose of food packaging applications. This research focused on two parts: (i) improving the toughness and flexibility of PLA by investigating the effect of addition of three different plasticizers, namely, polyethylene glycol (PEG), tri n-butyl citrate (TBC), and triacetin (TA) of different concentrations using cast solution method, and (ii) PLA/TA 10%, the best investigated combination among all in terms of mechanical properties, was then chosen as the base system to further investigate the effect of incorporating four different nano-reinforcements, namely, carbon nanotubes (CNT), COOH functionalized carbon nanotubes (CNTCOOH), graphene platelets (GNP), and COOH functionalized graphene nanoplatelets (GNPCOOH) of different concentrations for fabrication of PLA nanocomposites. The physical, chemical, and barrier properties of all prepared samples were investigated through the stress-relaxation measurements, DSC, TGA, Mercury Porosimetry, biodegradability, water absorption, oxygen permeability, and water vapour transmission. GNPCOOH nanocomposites exhibited the best mechanical behaviour among all samples, while TGA analysis revealed that it had no effect on the thermal stability. Results obtained by Hg porosimetry have shown that the total porosity has tremendously decreased by incorporation of the investigated nanofillers. The biodegradation of PLA nanocomposites in natural compost was investigated and it was observed that the incorporation of nanofillers had no specific effect on biodegradation of PLA nanocomposites. Water absorption test revealed that the functionalized nanofillers showed relative increase in water absorption as compared to pristine nanofillers. Oxygen permeability test showed that lower concentrations of GNPCOOH had higher oxygen diffusion, while higher concentrations revealed a remarkable decrease in oxygen permeability. Water vapour transmission test showed that the incorporation of nanofillers has considerably decreased the rate of water vapour transmission.